High‐Performance Bifunctional Electrocatalysts of Palladium Decoration on Carbon Nanoarchitectures for Indirect Releasing of H2 Stored in Formate. Issue 12 (13th October 2021) - Liu, Xi; Ji, Yaxin; Chen, Guangbo; Peng, Xinxin; Yi, Luocai; Chen, Junxiang; Feng, Xinliang; Wen, Zhenhai
Abstract : Formate has received tremendous research interest as one of the promising organic H2 carriers to store and transport H2 safely and economically. One paramount challenge for implementing the practical feasibility of formate as H2 carrier is how to release H2 at standard pressure and room temperature on demand. Herein, a proof‐of‐concept electrochemical strategy to indirectly release H2 stored in formate in a controlled manner is proposed, in which formate is electrocatalytically oxidized at the alkaline anode to release electrons, which is used for H2 generation at the acidic cathode. For this purpose, highly active bifunctional electrocatalysts with uniformly dispersed Pd nanoparticles supported on a conductive hollow dodecahedron N‐doped carbon network (Pd/hd‐NC), which not only shows one order of magnitude higher catalytic current density than the commercial Pd/C for alkaline formate oxidation reaction (FOR) but is comparable with the commercial Pt/C for acidic hydrogen evolution reaction (HER), are developed. A hybrid alkali/acid cell is developed using Pd/hd‐NC as anode and cathode catalysts of FOR and HER, respectively; in this way, H2 stored in formate can be indirectly released in a tunable manner, which presents significant steps forward, increasing the resiliency of formate as H2 carrier. Abstract : A bifunctional electrocatalyst with Pd nanoparticles supported on a conductive hollow dodecahedron N‐doped carbon network (Pd/hd‐NC) for alkaline formate oxidation reaction (FOR) and acidic hydrogen evolution reaction (HER) is designed. A hybrid alkali/acid cell is developed using the Pd/hd‐NC as anode and cathode catalysts; in this way, H2 stored in formate can be indirectly released in a tunable manner.